Late infantile neuronal ceroid lipofuscinosis with epilepsy as the first symptom: one case report - Jing XIAO (Chinese Journal of Contemporary Neurology and Neurosurgery, 2018)
DOI: 10.3969/j.issn.1672-6731.2018.06.011